EKSISTENSI PESANTREN KHALAF DI ERA 4.0 - Muhamad Arif; Mohd Kasturi Nor Abd Aziz (Institut Agama Islam Negeri (IAIN) Tulungagung, 2021)
Abstract: Islamic boarding schools are required to be able to answer the development of the world of technology, because of the existence of the world of technology that continues to grow. So, the right response for Islamic boarding schools to follow without losing their character becomes a necessity. There are three focus problems including, How does the existence of Darul Ihsan Islamic boarding school replace Gresik in strengthening the character of students in the era of the industrial revolution 4.0,? Second, what is the role of Darul Ihsan Menganti Islamic Boarding School in Gresik in the era of the industrial revolution 4.0? and Third, what are the inhibiting factors for the Darul Ihsan Menganti Gresik Islamic Boarding School in the 4.0 era? The research uses a qualitative case study approach, data collection techniques using interviews, observation and documentation. While the data analysis from Miles and Hubarman, in the form of condensation data, display data and conclusion drawing and verification. In the process of eliminating data that is still doubtful, the panelists use triangulation of methods, sources and theories. a solid foundation in following the development of civilization, in the form of five five souls of the cottage integrated with character education, in addition, the pesantren prepares a pillar in the form of four pillars, so that both must be juxtaposed with a wall in the form of four keys in navigating life. The four important roles of pesantren include education, religion, technology and economy. There are three inhibiting factors for pesantren in carrying out their existence.